Channels for Promoting Health Literacy on Family Planning Among Pregnant Women in Akheri Ward, Arumeru District (American Journal of Arts and Human Science, 2025)
The study assessed the channels utilized to enhance family planning literacy among pregnant women in Akheri Ward, Arumeru District, Tanzania, between February and April 2024. The research focuses on hospital-registered pregnant women and employs a mixed-methods approach to address the central question of how family planning information is effectively disseminated. A total sample of 269 respondents was selected using a combination of probability and non-probability sampling techniques. Data collection involved structured interviews with key informants, including Reproductive and Child Health Officers, as well as questionnaires administered to the target population.The findings reveal that antenatal clinic mobilization by health professionals serves as the most effective channel for disseminating family planning information. This approach is particularly valued for fostering trust, offering personalized education, and facilitating informed decision-making among pregnant women. Social media platforms, especially WhatsApp groups, emerge as the second most effective channel, providing convenient access to information. Additionally, mass media, such as radio, plays a significant role in reaching broader and often remote populations. However, barriers such as limited internet access, inadequate digital literacy, and time constraints pose challenges to the efficacy of these channels, particularly in rural settings. The study underscores the critical importance of a multi-channel communication strategy to ensure comprehensive dissemination of family planning knowledge, particularly for underserved rural communities. Recommendations include increased investment in both traditional media, such as radio, and digital platforms to expand access and overcome infrastructural barriers. Furthermore, capacity-building initiatives for health professionals and community-based interventions are advocated to improve engagement and enhance maternal health outcomes. These findings contribute to the broader discourse on maternal health literacy, highlighting the need for context-specific, inclusive communication strategies in low-resource settings.